2005
DOI: 10.1007/s00280-005-0008-5
|View full text |Cite
|
Sign up to set email alerts
|

Camptothecin analogs with enhanced activity against human breast cancer cells. II. Impact of the tumor pH gradient

Abstract: Human breast tumors often exist in an acidic and hypoxic microenvironment, which can promote resistance to radiation and chemotherapies. A tumor-selective pH gradient arises in these tumors which favors uptake and retention of drugs like camptothecin that are weak acids. We evaluated the effect of alkyl substitutions at the 7 position in seven CPTs with varying groups at the 10 position on modulation by acidic extracellular pH in three human breast cancer cell lines. Growth inhibition was assessed by propidium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…It is unlikely that the sensitization of colon carcinoma cells was mediated by interaction of NiK-12192 with the transporters (BCRP or P-glycoprotein), because it was detected in cells expressing either low (parental) or high levels (resistant sublines) of these proteins. However, because changes of acidification could influence the expression of these transport systems (Adams et al, 2006), an indirect effect mediated by protein down-regulation could not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that the sensitization of colon carcinoma cells was mediated by interaction of NiK-12192 with the transporters (BCRP or P-glycoprotein), because it was detected in cells expressing either low (parental) or high levels (resistant sublines) of these proteins. However, because changes of acidification could influence the expression of these transport systems (Adams et al, 2006), an indirect effect mediated by protein down-regulation could not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreating animals with bicarbonate before administering mitoxantrone or doxorubicin has been shown to increase the response of model CH3 or MCF7 breast cancers, respectively, without significantly increasing the pHe of normal muscle (90,94). The chemical structure of camptothecan has even been modified to take advantage of this pH-dependent partitioning across the plasma membrane to increase its antiproliferative effect (95,96). Although these approaches were successful in treating animal tumors, it is not clear if these acute approaches will yield long-term effectiveness without systemic acid base side effects during multicycle chemotherapy in humans.…”
Section: Manipulation Of Tumor Acidosismentioning
confidence: 99%
“…Gene expression changes have been identified that are a response to the acidotic environment of the tumor that may contribute to tumor progression. These induced genes include the acid-responsive angiogenic stimulator interleukin-8 (103), the bone remodeling parathyroid hormone/parathyroid hormone receptor pathway (104), the breast cancer resistance protein (96), and tumor necrosis factor-a (105). Additional mechanisms of gene regulation in response to acidity include induction of the Sp1 transcription factor (106) and specific increases in mRNA stability (107).…”
Section: Manipulation Of Tumor Acidosismentioning
confidence: 99%
“…The reduction potential of a ROS species formed in these reactions is generally lower in alkaline than in acidic conditions [36]. Previous studies have shown that lowering the pHe from 7.4 to 6.7 resulted in lowering of intracellular pH (pHi) from 7.4 to 6.9/7.0 [37,38]. The question whether the pHi difference in the range of 0.5-0.4 might result in the changes of intracellular ROS stability/reactivity deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%